The Reconstructed School - Pearson, Francis B. (Francis Bail), 1853-1938 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Reconstructed School" by Francis B. Pearson is an educational treatise written in the early 20th century. The work serves as a critical examination of the educational system, focusing on the need for a transformation in how schools operate to foster long-lasting personal and societal development. Pearson examines various constants and variables in educational practices, advocating for the enhancement of teacher effectiveness and a set of core qualities to be cultivated in students, such as integrity, imagination, and a sense of responsibility. At the start of "The Reconstructed School," Pearson outlines his vision for educational reform, emphasizing the importance of shared thinking among teachers, students, and the community to achieve common goals. He posits that achieving unity in thought leads to collective action, which ultimately contributes to societal betterment. The opening chapters discuss the shortcomings of traditional educational methods that fail to nurture individuality and initiative, calling for a shift towards more holistic and inclusive educational practices. Pearson$1 (Bs reflections on past and present educational philosophies set the stage for his broader argument aimed at redefining the purpose and processes of schooling in a way that better prepares students for active and engaged citizenship. (This is an automatically generated summary.)s
Release date is 2005-01-03
E-text prepared by Bill Tozier, Barbara Tozier, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Teaching; Education -- United States